Polish Music Published by Moeck 1958 to 1967 – a (Failed?) Transfer from East to West - Borchers, Sebastian (Res Facta Nova, 2020)
From the end of the 1950s, the West German publisher Moeck officially represented the state-led music publishing house PWM ‘in the West’ with the permission of the Polish Ministry of Culture. Beside the distribution of score editions and orchestral performance materials by the PWM, Moeck also represented the interests of Polish composers in the Federal Republic of Germany directly in his own catalogue. Among the first authors of the new series of editions were Kotoński, Lutosławski, Penderecki, Serocki and Szalonek. They belonged to a circle that regularly participated in West German musical life in the 1960s. Despite the spirit of optimism and advantages for the composers, this cooperation also led to problems on several levels. These included the billing of performance materials and the handling of international copyright. This made the participants aware of various limits and led to conflicts – especially on the Polish side. Translation of Polish texts in vocal works into German and English was also not as straightforward as originally planned. The article offers new insights into Polish–German cooperation in the cultural field of music, which went on despite the difficult relationship between the two states then and also beyond the borders of the Cold War.